2018
DOI: 10.1007/s11657-018-0470-4
|View full text |Cite
|
Sign up to set email alerts
|

Expressed information needs of patients with osteoporosis and/or fragility fractures: a systematic review

Abstract: SummaryThis systematic review identified patients have unmet information needs about the nature of osteoporosis, medication, self-management and follow-up. Clinician knowledge and attitudes appear to be of key importance in determining whether these needs are met. Unmet information needs appear to have psychosocial consequences and result in poor treatment adherence.PurposePatient education is an integral component of the management of osteoporosis, yet patients are dissatisfied with the information they recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 42 publications
2
61
0
1
Order By: Relevance
“…Understanding the patient's experience with the TM program in terms of barriers, facilitators, and needs in healthcare delivery will assist with future quality improvement initiatives, including the development of a selfmanagement program that is tailored to the unique needs of individuals with osteoporosis. Past research has indicated that programs that are derived from the patient perspective are associated with better outcomes [25]; future research could involve implementing and evaluating the program. Future research should evaluate health outcomes and performance indicators of participants in the OP TM program, comparing to those attending the clinic in person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the patient's experience with the TM program in terms of barriers, facilitators, and needs in healthcare delivery will assist with future quality improvement initiatives, including the development of a selfmanagement program that is tailored to the unique needs of individuals with osteoporosis. Past research has indicated that programs that are derived from the patient perspective are associated with better outcomes [25]; future research could involve implementing and evaluating the program. Future research should evaluate health outcomes and performance indicators of participants in the OP TM program, comparing to those attending the clinic in person.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [25] identified that people with osteoporosis want information about the nature of osteoporosis/ fracture risk, medication, self-management, and understanding the role of bone density test. In contrast to these results, our patients were less interested in learning about the nature of osteoporosis and medication, and more interested lifestyle factors and wellness strategies to cope with the emotional impact of the condition.…”
Section: Characteristicmentioning
confidence: 99%
“…(25) Finally, the 1-year mortality for hip-fracture patients ranges from 15% to 30% for community-dwelling residents (25,27,31) to 40% to 55% for long-term care facility residents. (33) To communicate riskrelated messages effectively, all health care professionals should provide consistent and sustained messaging throughout the care pathway, beginning at time of diagnosis and continuing repeatedly. (32) Thus, they are not likely to take appropriate steps to address their risk.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
“…(32) Thus, they are not likely to take appropriate steps to address their risk. (33) To communicate riskrelated messages effectively, all health care professionals should provide consistent and sustained messaging throughout the care pathway, beginning at time of diagnosis and continuing repeatedly. (4,5) These messages also should be communicated to family/caregivers.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
See 1 more Smart Citation